IS-LM Stability Revisited: Samuelson was Right, Modigliani was Wrong - Mendoza, Waldo (Economia, 2015)
In Hicks’s IS-LM model, where it is assumed that production is determined in the goods marketand the interest rate is determined in the money market, when the marginal propensity to spend is greater than one, the IS has a positive slope. Modigliani (1944), Varian (1977) and Sargent (1987) determined that in this special case the IS-LM model is stable when the LM slope isgreater than the IS.In line with Samuelson (1941), this article shows that in this case the model is stable when the IS slope is greater than the LM slope. However, in this stable case the model does not have a useful economic meaning.One solution to this theoretical problem is to abandon the Keynesian adjustment mechanism and replace it with the Classical mechanism where the interest rate is determined in the goods market and production is determined in the money market. In this case, the IS-LM model is stable when the LM is steeper than the IS.